Valmiki Ramayana Social Values and Their Impact on Life: Exploring the Ethical and Cultural Significance of Valmiki Ramayana (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The magnificent epic The Valmiki Ramayana gives advice on how to live a good life at eachstage of life. Various tough events arise in a person's life, and the Valmiki Ramayana demonstrates how tonavigate through them pleasantly and effortlessly. Lord Rama and Goddess Sita present an ideal fordealing with many forms of clashing situations and living a happy and healthy life in the ValmikiRamayana. Furthermore, their actions and lifestyles represent a variety of values, including moral,spiritual, intellectual, artistic, cultural, and other values that help us construct a healthier and bettersociety. Ramayn is an epic that serves as a basis for establishing values throughout the world for theperiod. Satyuga, Dwapryuga, Tretayuga, and Kalyuga are the four ages that largely contribute to societalevolution in the epic of Ramayan.